FACTORS AFFECTING THE PERFORMANCE OF LEARNERS IN ENGLISH LANGUAGE AT UCE IN GOVERNMENT AIDED SECONDARY SCHOOLS IN BUBIITA SUB-COUNTY, BUDUDA DISTRICT. - NEBOKHE VIOLET MAYANZA (My University, 2024)
ABSTRACT This study will examine the Factors affecting the performance of learners in English language at UCE in Government Aided Secondary Schools in Bubiita Sub-county, Bududa District. The purpose of the study is to examine the factors affecting the performance of learners in English language at UCE in Government Aided Secondary Schools in Bubiita Sub-county, Bududa District This study will be based on three objectives including: to analyze the teachers’ proficiency in English teaching; to examine the methods used by the teachers in the teaching of English language in the Bubiita Sub-county and to establish the instructional materials used by teachers to teach English language in Bubiita Sub-county. The study will adopt a descriptive research design. The study population will comprise 150 and data will be collected from 108 respondents using self-administered questionnaires with both quantitative and qualitative methods, interviews and observation checklists.